2020
DOI: 10.20944/preprints202006.0271.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-Related Potential to Conscious and Nonconscious Emotional Face Perception in Females with Autistic-Like Traits

Abstract: This study explored the electrocortical correlates of conscious and nonconscious perceptions of emotionally laden faces in neurotypical adult women with varying levels of autistic-like traits (Autism Spectrum Quotient - AQ). Event-related potentials (ERPs) were recorded during the viewing of backward-masked images for happy, neutral, and sad faces presented either below (16 ms - subliminal) or above the level of visual conscious awareness (167 ms - supraliminal). Sad compared to happy faces elicited larger fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…[12] reported that the amplitude of occipital N1 was enhanced in response to subliminal fearful face stimuli in TD, whereas this subliminal effect was negative in ASD. Meanwhile, other studies have reported enhanced N170 amplitude with delayed latency for subliminal emotional faces in ASD [13,21]. On the basis of the current results, taken together with these previous findings, we speculate that rapid processing of subliminal emotional prime faces in the amygdala might be impaired and that emotional information is processed but with a delayed or weakened projection from the amygdala to occipitotemporal face-specific areas in ASD, even if subliminal fearful faces affect the processing of subsequent supraliminal faces.…”
Section: Discussionmentioning
confidence: 98%
“…[12] reported that the amplitude of occipital N1 was enhanced in response to subliminal fearful face stimuli in TD, whereas this subliminal effect was negative in ASD. Meanwhile, other studies have reported enhanced N170 amplitude with delayed latency for subliminal emotional faces in ASD [13,21]. On the basis of the current results, taken together with these previous findings, we speculate that rapid processing of subliminal emotional prime faces in the amygdala might be impaired and that emotional information is processed but with a delayed or weakened projection from the amygdala to occipitotemporal face-specific areas in ASD, even if subliminal fearful faces affect the processing of subsequent supraliminal faces.…”
Section: Discussionmentioning
confidence: 98%